CUSTOMERS' SATISFACTION FACTORS OF ONLINE TRANSPORTATION SERVICES - Kurniawan, Yoga; Putritama, Afrida (Universitas Negeri Yogyakarta, 2020)
Abstract: Customers' Satisfaction Factors of Online Transportation Service. The purpose of this study is to determine the effect of quality of information system, quality of service, perceived security and perceived privacy on customer satisfaction in using online motorcycle transportation. This research is a survey based research with quantitative approach. The populations in this study are all users of Grab online motorcycle transportation services in Special Region of Yogyakarta. Sampling technique in this study used purposive sampling (non-probability sampling) with a total sample of 162 people. The data collection technique used an online questionnaire that has been qualified for validity and reliability. The data analysis method is multiple linear regression analysis methods. The results showed that there is partial positive effect between quality of information system, quality of service, perceived security, and perceived privacy of Grab customers' satisfaction. The four dependent variable simultanously showed a significant positive effect between customer satisfaction and the independent variable with value number of the coefficient of determination (adjusted R2) is 0,488, the value of the F-test results is 39.412> 2,868312 and significance 0.000. Keywords: Information Systems Quality, Service Quality, Perceived Security, Perceived Privacy, Customer Satisfaction